Reflexão acerca do uso da maquete como uma estratégia didática para o ensino de física - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The contemporary challenge is to seek alternative educational practices to mitigate the impacts of students' learning deficits, especially in the discipline of Physics. Therefore, there is a need to analyze current pedagogical practices. Thus, the present work has the general objective of analyzing selected articles about the model tool in the teaching of Physics with an approach within the school environment, having as specific objectives to understand how Physics has been worked within the classroom by teachers, and to discuss the articles with an emphasis on results, listing their contributions to the formation of scientific knowledge. The methodology of the work was based on a systematic bibliographical review in which two databases were used for the selection of articles. In this way, the results obtained in the discussions of the articles were: the social interaction between teacher/student, interdisciplinarity, in addition to the teacher having the pleasure of conducting a class with a didactic resource (model), thus having a dynamic and productive class.
Keywords: Práticas Educacionais; Maquete; Ensino de Física; CNPQ:: CIÊNCIAS EXATAS E DA TERRA